Label‐free monitoring and manipulation of microfluidic water‐in‐oil droplets. Issue 4 (10th October 2020) - Frey, Christoph; Pfeil, Jonas; Neckernuss, Tobias; Geiger, Daniel; Weishaupt, Klaus; Platzman, Ilia; Marti, Othmar; Spatz, Joachim P.
Abstract: Droplet‐based microfluidic technology offers several benefits: the integration of multiple laboratory functions into a single microfabricated chip, manual intervention possibilities, minimal sample consumption, and increased analysis speed and data precision. These advantages have boosted the widespread application of this technology in biological and biomedical research. Despite recent progress, considerable challenges remain to be addressed for end‐user applications. This especially concerns the difficulty of creating powerful and easy to implement methods for real‐time analysis and active manipulation of passing droplets. Toward this end, we developed a very sensitive optical device equipped with smart algorithms for real‐time label‐free monitoring and active manipulation of passing droplets. We demonstrate the advanced properties of the developed optical device by measuring different droplet production parameters as well as the label‐free detection of cells in droplets. Moreover, the newly developed technology was connected with a function generator system to allow for subsequent manipulation of the monitored droplets based on the measured parameters. As an example, we performed electric field‐mediated, label‐free sorting of cell‐containing droplets from empty ones. Furthermore, we achieved an efficient size‐based separation of droplets. We envision that the developed optical device will be a useful tool for the online monitoring of passing droplets and will be implemented for the integration and automation of various droplet‐based microfluidic functional units. Abstract : Achieving a precise control over the integration of several microfluidic operation modules requires for real‐time label‐free analysis and manipulation is a compelling goal. In this manuscript, a newly designed optical device for easy‐to‐implement label‐free observation, characterization, and active manipulation of passing water‐in‐oil droplets in kHz rates has been developed. The developed device allows for a controlled label‐free droplet manipulation according to different pre‐set criteria.